2019
DOI: 10.5194/amt-12-1935-2019
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ionization quadrupole mass spectrometer with an electrical discharge ion source for atmospheric trace gas measurement

Abstract: Abstract. We present a chemical ionization quadrupole mass spectrometer (CI-QMS) with a radio-frequency (RF) discharge ion source through N2∕CH3I as a source of primary ions. In addition to the expected detection of PAN, peracetic acid (PAA) and ClNO2 through well-established ion–molecule reactions with I− and its water cluster, the instrument is also sensitive to SO2, HCl and acetic acid (CH3C(O)OH) through additional ion chemistry unique to our ion source. We present ionization schemes for detection of SO2, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 70 publications
2
31
0
Order By: Relevance
“…Nitryl chloride (ClNO 2 ), hydrogen chloride (HCl), and sulfur dioxide (SO 2 ) were detected with a chemical ionization quadrupole mass spectrometer (CI-QMS) using an electrical, radio-frequency (RF) discharge ion source. The instrument and the ion-molecule reactions involved in the detection of the above-mentioned trace gases are described in detail by Eger et al (2019). Briefly, ClNO 2 was monitored as I•ClNO − 2 at a mass-to-charge ratio (m/z) of 208 and 210 subsequent to the reaction of ClNO 2 with I − (McNeill et al, 2006;Osthoff et al, 2008;Thornton et al, 2010).…”
Section: Measurement Of Clno 2 Hcl and Somentioning
confidence: 99%
See 3 more Smart Citations
“…Nitryl chloride (ClNO 2 ), hydrogen chloride (HCl), and sulfur dioxide (SO 2 ) were detected with a chemical ionization quadrupole mass spectrometer (CI-QMS) using an electrical, radio-frequency (RF) discharge ion source. The instrument and the ion-molecule reactions involved in the detection of the above-mentioned trace gases are described in detail by Eger et al (2019). Briefly, ClNO 2 was monitored as I•ClNO − 2 at a mass-to-charge ratio (m/z) of 208 and 210 subsequent to the reaction of ClNO 2 with I − (McNeill et al, 2006;Osthoff et al, 2008;Thornton et al, 2010).…”
Section: Measurement Of Clno 2 Hcl and Somentioning
confidence: 99%
“…HCl was observed as I(CN)Cl − (m/z 188 and 190) (Eger et al, 2019) with a sensitivity of 0.17 Hz pptv −1 per 10 6 Hz of I − at m/z 188 (and 0.05 Hz pptv −1 at m/z 190), a detection limit of 98 pptv, and a total measurement uncertainty of 20 % ± 72 pptv. As m/z 190 suffers from known interferences (e.g.…”
Section: Measurement Of Clno 2 Hcl and Somentioning
confidence: 99%
See 2 more Smart Citations
“…They influence the acidity of aerosols and cloud droplets and are involved in the formation of secondary organic aerosols (SOAs), thereby impacting air quality and climate (Kanakidou et al, 2005;Hallquist et al, 2009). Pyruvic acid, CH 3 C(O)C(O)OH, the simplest α-keto acid, is omnipresent in plants, where it is central to the metabolism of isoprene, monoterpenes and sesquiterpenes (Eisenreich et al, 2001;Magel et al, 2006;Jardine et al, 2010), and is also found in tropospheric air, especially in the boundary layer of vegetated regions (see Sect. 1.3).…”
Section: Introductionmentioning
confidence: 99%